Matrix metalloproteinase expression levels suggest distinct enzyme roles during lumbar disc herniation and degeneration - Bachmeier, Beatrice E. (Springer-Verlag, 2009)
The disruption of the extracellular disc matrix is a major hallmark of disc degeneration. This has previously been shown to be associated with an up-regulation of major matrix metalloproteinase (MMP) expression and activity. However, until now hardly any data are available for MMP/TIMP regulation and thereby no concept exists as to which MMP/TIMP plays a major role in disc degeneration. The objective of this study was, therefore, to identify and quantify the putative up-regulation of MMPs/TIMPs on the mRNA and protein level and their activity in disc material in relation to clinical data and histological evidence for disc degeneration. A quantitative molecular analysis of the mRNA expression levels for the MMPs (MMPs-1, -2, -3, -7, -8, -9, -13) and the MMP inhibitors (TIMPs-1 and -2) was performed on 37 disc specimens obtained from symptomatic disc herniation or degeneration. In addition, disc specimens from patients without disc degeneration/herniation (=controls) were analyzed. Expression of MMPs-1, -2, -3, -7, -8, -9, -13 and TIMPs-1, -2 was analyzed using quantitative RT-PCR, normalized to the expression level of a house keeping gene (GAPDH). Gene expression patterns were correlated with MMP activity (in situ zymography), protein expression patterns (immunohistochemistry), degeneration score (routine histology) and clinical data. MMP-3 mRNA levels were consistently and substantially up-regulated in samples with histological evidence for disc degeneration. A similar but less pronounced up-regulation was observed for MMP-8. This up-regulation was paralleled by the expression of TIMP-1 and to a lesser extent TIMP-2. In general, these findings could be confirmed with regard to protein expression and enzyme activity. This study provides data on the gene and protein level, which highlights the key role of MMP-3 in the degenerative cascade leading to symptomatic disc degeneration and herniation. Control of the proteolytic activity of MMP-3 may, therefore, come into the focus when aiming to develop new treatment options for early disc degeneration.